SELFCARE REQUIREMENTS OF TRANSSEXUAL WOMEN USING SEX HORMONES, ACCORDING TO THE OREM SELFCARE THEORY - Carla Andreia Alves de Andrade; Andréa Roges Loureiro; Esmeraldo Rodrigues de Lima Neto; Eliane Maria Ribeiro de Vasconcelos; Ednaldo Cavalcante de Araújo (Universidade Federal do Paraná, 2018)
Objective: to identify self-care needs of transsexual women using sex hormones, based in Orem's General Theory of Nursing. Method: descriptive-exploratory study with a qualitative approach, undertaken in Recife, capital of the Brazilian state of Pernambuco, between November 2016 and February 2017. Data collection was undertaken through semistructured interviews, with a sample of 10 transsexual women using sex hormones, selected using the Snowball technique. Analysis was undertaken using the IRAMUTE Q software, version 0.7. Results: the needs found were: prevention of danger to life, functioning and well-being; seeking and ensuring appropriate medical care; adapting to the changes in the body; modification of self-image; and adverse events affecting development. Conclusion: the re-quirements were anchored in issues caused by poor knowledge about the use of hormones, and by the poor quality of the information received through the health professionals.